An in vitro FRET-based assay for the analysis of SUMO conjugation and isopeptidase cleavage - Stankovic-Valentin, Nicolas; Kozaczkiewicz, Lukasz; Curth, Katja; Melchior, Frauke (SUMO Protocols, 2009)
To measure rates of sumoylation and isopeptidase cleavage in vitro, we developed an enzyme assay that is based on fluorescence resonance energy transfer (FRET). FRET is a process by which the excited state energy of a fluorescent donor molecule is transferred to an acceptor molecule. Efficient energy transfer requires very close proximity, and can therefore be used as a read-out for covalent and non-covalent protein interactions. The assay described here uses bacterially expressed and purified YFP-SUMO-1 and CFP-RanGAP1 as model substrates that are covalently coupled in the presence of recombinant SUMO E1 and E2 enzymes and ATP. Reactions of 25 microl volume, set up in 384-wells plates, give sufficient signal for analysis. Consequently, this assay requires very low amounts of recombinant proteins and allows measurement of time courses in high-throughput format.
Gesehen am 04.09.2023